Attracting, integrating, selecting? : Reflections on the recognition of foreign qualifications in different contexts ; [paper presented at the 9th International Conference on Researching Work & Learning, 9-11 December 2015, Singapore] - Eberhardt, Christiane [Verfasser]; Annen, Silvia [Verfasser] (My University, 2015)
"How can a professional or vocational qualification acquired abroad be recognised? Against the background of an impending shortage of skilled workers and negative demographic developments, this is a question which has had a role to play in Germany for some time now. In order to meet the demands of the German labour market by providing it with the skilled workers it needs, the so-called Recognition Act entered into force in April 2012. 'Recognition' in this context is understood as a formal procedure assessing the qualification acquired abroad towards the German occupation. Some fundamental questions are linked with the implementation of recognition practices: How much information is required in order to assess a qualification as 'equivalent' with a domestic one? How do countries with a long history of immigration approach the recognition of vocational qualifications and which procedures are in place? What are the perceived challenges to be faced? Some of these issues are addressed by the project 'Models and procedures for the recognition of vocational qualifications and competences acquired abroad' (MoVA)." In this paper, the authors provide a report at the halfway stage of the MoVA project and present initial reflections on terminological, methodological and on content specific challenges that emerged in the research process. The paper concludes with some remarks on the function that is accorded to recognition in various contexts. (Authors' abstract, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; I 2.3.5 Australien, Ozeanien; Anrechnung von Bildungsleistungen; Anerkennungsgesetz; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Kanada; Australien